Joining the supply chain: A firm-level perspective from Southeast Asia - Ganeshan Wignaraja (Indian Council for Research on International Economic Relations (ICRIER), 2014)
This paper undertakes a comparative, firm-level analysis of joining the supply chain in five Southeast Asian economies to improve our understanding of fragmentation of manufacturing across borders. The research maps supply chains and conducts firm-level econometric analysis on 5,900 enterprises. The findings suggests that firm size (reflecting economies of scale to overcome entry costs) matters for joining supply chains with large firms playing the dominant role in Southeast Asian economies. Meanwhile, small and medium enterprises (SMEs) make a small contribution to supply chain activity relatively to the sectors employment or GDP contribution in South East Asian economies. However, firm size is not the whole story. Efficiency - particularly investment in building technological capabilities and skills - and access to commercial bank credit also influence jo ining supply chains. The paper suggests that governments can facilit ate SMEs joining supply chains through a market-oriented strategy for SMEs, modern physical infrastructure, streamlined bureaucratic procedures and good quality business support services.
Keywords: F1; F2; F21; F23; F43; L25; O31; 330; Global supply chains; firm-level analysis; firm size; SMEs; technological capabilities; access to finance; policy and business environment; South East Asia